Dysfunction of macrophages leads to diabetic bone regeneration deficiency - Shen, Yufeng; Zhang, Yifan; Zhou, Zheng; Wang, Jinyu; Han, Dong; Sun, Jiwei; Chen, Guangjin; Tang, Qingming; Sun, Wei; Chen, Lili (Frontiers in Immunology, 2022)
Insufficient bone matrix formation caused by diabetic chronic inflammation can result in bone nonunion, which is perceived as a worldwide epidemic, with a very high socioeconomic burden on public health systems. Macrophages in microenvironment orchestrate the inflammation and launch the process of bone remodeling and repair, but the aberrant macrophages can drive drastic inflammatory responses during diabetic bone regeneration. In diabetes mellitus, the proliferation of resident macrophages in bone microenvironment is limited, while enhanced myeloid differentiation of hematopoietic stem cells (HSCs) leads to increased and constant monocyte recruitment and thus macrophages shift toward the classic pro-inflammatory phenotype, which leads to the deficiency of bone regeneration. In this review, we systematically summarized the origin of aberrant macrophages under diabetic conditions. Moreover, we evaluated the deficit of pro-regeneration macrophages in the diabetic inflammatory microenvironment. Finally, we further discussed the latest developments on strategies based on targeting macrophages to promote diabetic bone regeneration. Briefly, this review aimed to provide a basis for modulating the biological functions of macrophages to improve bone regeneration and rescue diabetic fracture healing in the future.